Evaluation of allelopathic effects of Parthenium hysterophorus l. methanolic extracts on some selected plants and weeds - Bashar, H. M. Khairul; Juraimi, Abdul Shukor; Ahmad-Hamdani, Muhammad Saiful; Uddin, Md. Kamal; Asib, Norhayu; Anwar, Md. Parvez; Rahaman, Ferdoushi; Haque, Mohammad Amdadul; Hossain, Akbar (Public Library of Science, 2023)
Herbicides made from natural molecules are cost-effective and environmentally friendly alternatives to synthetic chemical herbicides for controlling weeds in the crop field. In this context, an investigation was carried out to ascertain the allelopathic potential of Parthenium hysterophorus L. as well as to identify its phenolic components which are responsible for the allelopathic effect. During the observation, the rate of germination and seedlings’ growth of Vigna subterranea (L.) Verdc, Raphanus sativus (L.) Domin, Cucurbita maxima Duchesne., Cucumis sativus L., Solanum lycopersicum L., Capsicum frutescens L., Zea mays L., Abelmoschus esculentus (L.) Moench, Daucus carota L., Digitaria sanguinalis (L.) Scop and Eleusine indica (L.) Gaertn were investigated by using methanol extracts, isolated from leaf, stem and flower of P. hysterophorus. Six concentrations (i.e., 25, 50, 75, 100, and 150 g L-1) of methanol extracts were isolated from P. hysterophorus leaf, stem and flower were compared to the control (distilled water). It was also observed that the concentration of methanol extracts (isolated from P. hysterophorus leaf, stem, and flower) while increased, the rate of seed germination and seedling growth of both selected crops and weeds decreased drastically, indicating that these methanol extracts have allelopathic potential. The allelopathic potential of P. hysterophorus leaf extraction (811) was found higher than the extraction of the stem (1554) and flower (1109), which is confirmed by EC50 values. The principal component analysis (PCA) was also used to re-validate the allelopathic potentiality of these methanol extracts and confirmed that Raphanus sativus, Solanum lycopersicum, Capsicum frutescens, Abelmoschus esculentus, Daucus carota, Digitaria sanguinalis, and Eleusine indica were highly susceptible to allelochemicals of P. hysterophorus. Besides these, the LC-MS analysis also revealed that the P. hysterophorus leaf extract contained 7 phenolic compounds which were responsible for the inhibition of tested crops and weeds through allelopathic effect. The results of the current study revealed that the leaf of P. hysterophorus is a major source of allelopathic potential on crops and weeds and which could be used as a valuable natural herbicide in the future for the sustainability of crop production through controlling weeds.